Multifunctional anti-fouling, dirt-resistant and acid-alkali-resistant water-based paint as well as preparation method and application method thereof

Through the modified monomer and nanocomposite technology, combined with the dynamic release anti-mold mechanism, the problem of insufficient wear resistance, adhesion and mildew resistance of water-based coatings is solved, and high adhesion, wear resistance and ultra-long-term prevention is achieved. Mold performance, multifunctional water-based coating with self-cleaning and self-repairing properties.

CN119264750APending Publication Date: 2025-01-07ZHEJIANG XINGHUI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411632292.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing water-based coatings have shortcomings in wear resistance, adhesion and mildew resistance, especially in strong acid and alkali environments, and traditional mildew anti-aging agents are not durable enough and are easily lost in humid environments.

Method used

Using modified monomer and nanocomposite technology with special structures, it provides continuous contact bactericidal and povitri-iodine complex releases active ingredients through quaternary ammonium groups, combining specific proportions of methyl acrylate-propylene The amide terpolymerization system forms a gradient transition layer and multiple protection mechanism to improve the chemical resistance and mildew resistance of the coating.

Benefits of technology

It achieves excellent adhesion, wear resistance and ultra-long-term mildew resistance of the coating, has self-cleaning and self-repairing properties, excellent storage stability, and significantly improves the overall performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136235100000141
    Figure BDA0005136235100000141
  • Figure BDA0005136235100000142
    Figure BDA0005136235100000142
  • Figure BDA0005136235100000151
    Figure BDA0005136235100000151
Patent Text Reader

Abstract

The invention relates to the technical field of water-based coatings, in particular to a multifunctional anti-fouling, dirt-resistant and acid-base-resistant water-based coating and a preparation method thereof.The multifunctional anti-fouling, dirt-resistant and acid-base-resistant water-based coating is prepared from, by weight, 70-80 parts of acrylic emulsion, 0.5-1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride, 1-3 parts of 3-glycidyloxypropyltrimethoxysilane, 1-3 parts of sodium dodecyl sulfate, 1-3 parts of sodium dodecyl sulfate, 1-3 parts of sodium dodecyl sulfate, 1-3 parts of sodium dodecyl sulfate, 1-3 parts of sodium The coating is prepared from the following components in parts by weight: 0.2 to 0.6 part of a povidone-iodine compound, 0.2 to 0.6 part of a polydimethylsiloxane defoaming agent, 0.3 to 0.8 part of a polyether modified polysiloxane flatting agent, 4 to 10 parts of a coalescing agent, 0.2 to 1 part of a nano silicon dioxide modified wax wear-resistant additive, 3 to 5 parts of polytetrafluoroethylene wax emulsion, 0.1 to 0.2 part of a mildew-proof bactericide, 0.2 to 0.6 part of a nonionic polyether wetting agent and 60 to 70 parts of water. Wherein the coating shows excellent adhesive force and wear resistance, the adhesive force reaches grade 0, and the Talbot wear-resistant mass loss is as low as 45 mg.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based coatings, and in particular to a multifunctional anti-fouling, dirt-resistant, acid- and alkali-resistant water-based coating and a preparation method thereof. Background Art

[0002] With the continuous improvement of environmental protection requirements, water-based paints are widely used in the fields of wood floor paint, tile paint and floor paint due to their low VOC emissions and environmental friendliness. However, there are still many technical difficulties in the practical application of existing water-based paints. In the prior art, acrylic emulsion is usually used as the main film-forming substance. Although it has certain weather resistance and mechanical strength, the wear resistance and adhesion of the coating are insufficient due to the weak interaction between molecular chains. In particular, it performs poorly in terms of interface bonding with smooth substrates and is prone to peeling.

[0003] At the same time, the characteristic of water-based systems that they are prone to microbial growth also poses a challenge to the long-term mildew prevention of coatings. Although the commonly used isothiazolinone mildew inhibitors can provide initial protection, they are not durable enough and are easily lost in humid environments. In addition, traditional water-based coatings have poor chemical resistance, especially in strong acid and alkali environments, which is prone to degradation, seriously affecting their service life.

[0004] The prior art also attempts to improve coating performance by adding various functional additives, such as adding wax emulsion to improve wear resistance, adding silane coupling agent to improve adhesion, etc. However, these modification methods are often simple physical mixing, lacking effective molecular design and interface regulation, and the synergistic effect between the components is not obvious, and phase separation is prone to occur during storage. Summary of the invention

[0005] In view of the above problems, the present invention proposes an innovative multifunctional anti-fouling, dirt-resistant, acid- and alkali-resistant water-based coating formula and a preparation method thereof.

[0006] The object of the present invention is to provide a multifunctional anti-fouling, dirt-resistant, acid-base-resistant water-based paint for finishing the surface of wood floor paint, tile paint or floor paint, which comprises, by weight:

[0007] 70-80 parts of acrylic emulsion, 0.5-1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride, 1-3 parts of 3-glycidyloxypropyl trimethoxy silane, 0.2-0.6 parts of povidone-iodine complex, 0.2-0.6 parts of polydimethylsiloxane defoamer, 0.3-0.8 parts of polyether modified polysiloxane leveling agent, 4-10 parts of film-forming aid, 0.2-1 parts of nano-silicon dioxide modified wax wear-resistant additive, 3-5 parts of polytetrafluoroethylene wax emulsion, 0.1-0.2 parts of mildew and fungicide, 0.2-0.6 parts of non-ionic polyether wetting agent, 60-70 parts of water;

[0008] Wherein, the acrylic emulsion is an acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion with a solid content of 50%-60%.

[0009] Preferably, the film-forming aid is selected from ethylene glycol butyl ether, propylene glycol methyl ether and mixtures thereof;

[0010] The mildew-proofing and fungicide is a mixture of isothiazolinone and hexamidine di(hydroxyethylsulfonic acid) salt in a weight ratio of 1:1;

[0011] The nano-silicon dioxide modified wax wear-resistant additive is prepared by mixing polyethylene wax and hydrophobic modified silicon dioxide with a particle size of 20-50 nm in a weight ratio of 95:5.

[0012] Preferably, in the acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion, the mass ratio of acrylic acid, methyl methacrylate and acrylamide is 60:35:5, and the solid content is 55%.

[0013] Preferably, the added amount of the methacryloyloxyethyltrimethylammonium chloride is 1 part,

[0014] The amount of 3-glycidyloxypropyltrimethoxysilane added is 2 parts,

[0015] The added amount of the povidone-iodine complex is 0.4 parts.

[0016] The preparation method of the water-based coating comprises the following steps:

[0017] (1) Preparation of modified monomers:

[0018] 3-Glycidyloxypropyltrimethoxysilane was hydrolyzed at pH 4-5 and 25°C for 2 h;

[0019] Methacryloxyethyltrimethylammonium chloride and hydrolyzed 3-glycidyloxypropyltrimethoxysilane were premixed at 40 °C for 1 h;

[0020] (2) Preparation of modified wear-resistant additives:

[0021] The polyethylene wax was melted at 80°C, hydrophobically modified silica was added, dispersed at high speed for 30 minutes, and then cooled and crushed;

[0022] (3) Grouping and mixing:

[0023] The first group: water, a nonionic polyether wetting agent and the modified monomer obtained in step (1);

[0024] The second group: acrylic emulsion, polytetrafluoroethylene wax emulsion, the modified wear-resistant additive obtained in step (2) and polydimethylsiloxane defoaming agent;

[0025] The third group: povidone-iodine complex, mildew-proof fungicide and polyether-modified polysiloxane leveling agent;

[0026] (4) Add the three mixtures into the reactor in sequence and stir at 1000-1200 rpm for 40 min;

[0027] (5) Grinding with a sand mill at a rotation speed of 2000-2500 rpm for 30-40 min, controlling the grinding fineness to be ≤30 μm, to obtain the water-based coating.

[0028] Preferably, the preparation method of the hydrophobically modified silica is:

[0029] The fumed silica was vacuum dried at 110-130°C for 2 h, dimethyldichlorosilane was added, refluxed under nitrogen protection for 4 h, filtered, washed with toluene 3 times, and dried at 80°C for 12 h.

[0030] Preferably, the nonionic polyether wetting agent is a polyoxyethylene-polyoxypropylene block copolymer, wherein the mass ratio of the polyoxyethylene segment to the polyoxypropylene segment is 40:60.

[0031] The water-based paint application method comprises mixing the water-based paint and the curing agent in a weight ratio of 20:1 and then applying the mixture.

[0032] Wherein, the curing agent is selected from at least one of a water-based epoxy resin curing agent and a water-based polyurethane curing agent.

[0033] Preferably, the viscosity of the water-based paint during application is 150-300 K.CUs, and the pH value is 9-10.

[0034] The coating curing temperature is 25-30°C, the relative humidity is 50-70%, and the curing time is 24h.

[0035] Preferably, the curing agent is a modified waterborne epoxy resin curing agent, which is prepared by reacting epoxy resin with a water-soluble amine at an equivalent ratio of 1:1.2 and emulsifying with a nonionic surfactant.

[0036] The present invention proposes an innovative design idea for water-based coating formula. By introducing a modified monomer with a special structure, the epoxy group and quaternary ammonium salt group on the molecular chain are used to form a chemical bond with the substrate and the coating molecules to form a gradient transition layer at the interface. At the same time, the hydrophobic modified silica is compounded with a wax additive through nanocomposite technology to form a wear-resistant system with a synergistic enhancement effect.

[0037] In terms of mildew prevention, the present invention designs a multiple protection mechanism based on the principle of dynamic release. The quaternary ammonium salt group provides a continuous contact bactericidal effect, and the povidone-iodine complex releases active ingredients under external stimulation to achieve long-term protection. This intelligent responsive mildew prevention system is significantly better than the protection effect of traditional single mildew inhibitors.

[0038] At the molecular design level, the present invention adopts a ternary copolymer system of acrylic acid, methyl methacrylate and acrylamide in a specific ratio, and achieves a balance of coating hardness, toughness and chemical resistance by regulating the content of different functional groups. Among them, acrylic acid provides excellent weather resistance and chemical resistance, methyl methacrylate contributes sufficient hardness, and the introduction of a small amount of acrylamide enhances the interaction between molecules through hydrogen bonding.

[0039] It is particularly worth mentioning that the present invention also has an innovative design in the preparation process. By controlling the degree of hydrolysis of the silane group, it is ensured that it forms the best chemical bond with the substrate; the multi-step dispersion process is adopted to avoid mutual interference between the functional components, which significantly improves the stability of the system.

[0040] Compared with the prior art, the multifunctional anti-fouling, dirt-resistant, acid-base-resistant water-based coating and the preparation method thereof of the present invention can achieve the following beneficial effects:

[0041] 1. The coating exhibits excellent adhesion and wear resistance, with adhesion reaching level 0 and Taber wear mass loss as low as 45 mg;

[0042] 2. It has super long-lasting mildew-proof performance and can still maintain the 0-level mildew-proof effect after 28 days;

[0043] 3. Formed a unique self-cleaning surface with a contact angle of 118°;

[0044] 4. It exhibits unexpected self-repairing properties and can repair minor scratches by itself;

[0045] 5. Excellent storage stability, no stratification after 60 days.

[0046] The significant improvement of these properties is due to the multiple synergistic effects formed between the functional components, which fully reflects the breakthrough of the present invention in molecular design and process innovation. Compared with the prior art, the present invention not only solves multiple technical problems in the field of water-based coatings, but also realizes some unexpected functional characteristics, which has important practical value. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] A multifunctional water-based paint that is stain-resistant, dirt-resistant, and acid-alkali-resistant is used for finishing the surface of wood floor paint, tile paint, or floor paint. The specific preparation method includes the following steps:

[0050] First, prepare a modified monomer. Hydrolyze 2 parts of 3-glycidyloxypropyltrimethoxysilane at pH 4.0 and 25°C for 2 hours to obtain a hydrolyzate; premix 1 part of methacryloyloxyethyltrimethylammonium chloride with the hydrolyzate at 40°C for 1 hour to obtain a modified monomer. Preferably, the modified monomer has a bifunctional property, wherein the silane group can form a chemical bond with the substrate, and the epoxy group can participate in the cross-linking reaction, thereby forming a strong chemical bond between the substrate and the coating.

[0051] Secondly, prepare the modified wear-resistant additive. The polyethylene wax was melted at 80°C, and hydrophobically modified silica with a particle size of 20 nm was added, with a mass ratio of 95:5. After high-speed shear dispersion for 30 minutes, the mixture was cooled and crushed to obtain 0.8 parts of nano-modified wear-resistant additive. It is worth noting that the introduction of nano-silica can significantly improve the wear resistance of the coating, which is mainly attributed to the reinforcing effect of nanoparticles in the polymer matrix.

[0052] Then, the raw materials were weighed according to the following proportions: 75 parts of acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion (monomer mass ratio 60:35:5, solid content 55%), 0.4 parts of polydimethylsiloxane defoamer, 0.5 parts of polyether modified polysiloxane leveling agent, 7 parts of ethylene glycol butyl ether film-forming aid, 4 parts of polytetrafluoroethylene wax emulsion, 0.15 parts of a 1:1 mixed mildew and fungicide of isothiazolinone and hexamidine di(hydroxyethyl sulfonic acid) salt, 0.4 parts of a polyoxyethylene-polyoxypropylene block copolymer (polyoxyethylene segment to polyoxypropylene segment mass ratio 40:60) wetting agent, 0.4 parts of a povidone-iodine complex, and 65 parts of water.

[0053] Next, the components are mixed in groups. The above components are divided into three groups: the first group is water, wetting agent and modified monomer; the second group is acrylic emulsion, polytetrafluoroethylene wax emulsion, modified wear-resistant additive and defoaming agent; the third group is povidone-iodine complex, mildew-proof fungicide and leveling agent. In particular, this grouping method can effectively avoid mutual interference between the components and ensure the stability of the final product.

[0054] Finally, the three groups of mixtures were added to the reactor in sequence, stirred at a rotation speed of 1000 rpm for 40 minutes, and ground with a sand mill at a rotation speed of 2000 rpm for 35 minutes, with the grinding fineness controlled to be 25 μm, to obtain the water-based coating.

[0055] Application method:

[0056] The water-based coating prepared above is mixed with a water-based epoxy resin curing agent in a weight ratio of 20:1, wherein the preparation method of the water-based epoxy resin curing agent is as follows: bisphenol A epoxy resin and water-soluble amine are reacted in an equivalent ratio of 1:1.2, and polyoxyethylene nonylphenol ether with an HLB value of 12 is used as a non-ionic surfactant for emulsification to obtain a water-based epoxy resin curing agent with a solid content of 60%.

[0057] Before construction, it is preferred to pre-treat the substrate surface: first, use 180-grit sandpaper to polish the substrate surface to remove the floating slurry and peeling, and then wipe it clean with a dust-free cloth. Then adjust the coating viscosity to 180K.CUs and the pH value to 9.5. Use a special brush or spray equipment for coating, and control the coating thickness to 150-180μm. Curing for 24 hours at a temperature of 28°C and a relative humidity of 60%.

[0058] Preferably, the water-based coating of this embodiment has excellent construction performance, wherein the synergistic effect of the defoamer and the leveling agent ensures the flatness of the coating surface, and the addition of the film-forming aid provides a suitable leveling time. The cured coating exhibits the following characteristics: pencil hardness reaches 2H; adhesion grade is 0; wear resistance (Taber abrasion 1000 turns) mass loss ≤ 50mg; acid resistance: no abnormality after immersion in 10% sulfuric acid for 24h; alkali resistance: no abnormality after immersion in 10% sodium hydroxide for 24h; mildew resistance reaches 0 grade.

[0059] These excellent properties are mainly derived from the synergistic effect of various functional components: the chemical bonding provided by the modified monomer enhances the adhesion of the coating; the compounding of nano-modified wear-resistant additives and polytetrafluoroethylene wax emulsion significantly improves the surface wear resistance; and the dual antibacterial system of antifungal and fungicide and povidone-iodine complex ensures a long-lasting antifungal effect.

[0060] In particular, the selection of the ternary copolymer emulsion in this embodiment plays a key role in the coating performance: acrylic acid provides excellent weather resistance and chemical resistance, methyl methacrylate gives the coating good hardness, and the introduction of a small amount of acrylamide improves the adhesion of the coating through hydrogen bonding. The synergistic effect of the three makes the coating have excellent comprehensive performance.

[0061] Example 2

[0062] A multifunctional water-based paint that is stain-resistant, dirt-resistant, and acid-alkali-resistant is used for finishing the surface of wood floor paint, tile paint, or floor paint. The specific preparation method includes the following steps:

[0063] First, prepare a modified monomer. Hydrolyze 1 part of 3-glycidyloxypropyltrimethoxysilane at pH 4.5 and 25°C for 2 hours to obtain a hydrolyzate; premix 0.5 parts of methacryloyloxyethyltrimethylammonium chloride with the hydrolyzate at 40°C for 1 hour to obtain a modified monomer. By controlling the hydrolysis pH and temperature, the degree of hydrolysis of the silane group can be optimized, thereby improving its ability to bind to the substrate.

[0064] Secondly, prepare a modified wear-resistant additive. Polyethylene wax was melted at 80°C, and hydrophobically modified silica with a particle size of 35 nm was added, with a mass ratio of 95:5. After high-speed shear dispersion for 30 minutes, the mixture was cooled and crushed to obtain 0.2 parts of a nano-modified wear-resistant additive. It is worth noting that a relatively small amount of wear-resistant additive was used in this embodiment, mainly considering the compatibility with other components.

[0065] Then, the raw materials were weighed according to the following proportions: 70 parts of acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion (monomer mass ratio 65:30:5, solid content 50%), 0.2 parts of polydimethylsiloxane defoamer, 0.3 parts of polyether modified polysiloxane leveling agent, 4 parts of propylene glycol methyl ether film-forming aid, 3 parts of polytetrafluoroethylene wax emulsion, 0.1 parts of a 1:1 mixed mildew and fungicide of isothiazolinone and hexamidine di(hydroxyethyl sulfonic acid) salt, 0.2 parts of a polyoxyethylene-polyoxypropylene block copolymer (polyoxyethylene segment to polyoxypropylene segment mass ratio 45:55) wetting agent, 0.2 parts of a povidone-iodine complex, and 70 parts of water.

[0066] Preferably, this embodiment uses an emulsion system with a relatively low solid content, and balances the hardness and flexibility of the coating by adjusting the monomer ratio. Increasing the proportion of acrylic acid can improve weather resistance, while appropriately reducing the content of methyl methacrylate is conducive to improving the flexibility of the coating.

[0067] Next, group mixing was performed. The above components were divided into three groups: the first group was water, wetting agent and modified monomer; the second group was acrylic emulsion, polytetrafluoroethylene wax emulsion, modified wear-resistant additive and defoaming agent; the third group was povidone-iodine complex, mildew-proof fungicide and leveling agent. The three groups of mixtures were added to the reactor in sequence and stirred at 1200 rpm for 40 minutes;

[0068] Finally, a sand mill was used to grind the mixture at a rotation speed of 2500 rpm for 30 min, and the grinding fineness was controlled to be 30 μm, thereby obtaining the water-based coating.

[0069] Application method:

[0070] The water-based coating prepared above was mixed with a water-based polyurethane curing agent at a weight ratio of 20:1, wherein the water-based polyurethane curing agent was prepared by reacting an isocyanate trimer with a polyether polyol and emulsifying with a nonionic surfactant, and had a solid content of 55%.

[0071] During construction, after grinding the surface of the substrate, adjust the coating viscosity to 150K.CUs and the pH value to 9.0. Use roller coating to control the coating thickness to 120-150μm. Curing for 24 hours at a temperature of 25℃ and a relative humidity of 50%.

[0072] The coating prepared in this embodiment has excellent comprehensive properties, among which: the pencil hardness reaches H; the adhesion grade is 1; the wear resistance (Taber abrasion 1000 turns) mass loss is ≤60mg; acid resistance: no abnormality after immersion in 5% sulfuric acid for 24h; alkali resistance: no abnormality after immersion in 5% sodium hydroxide for 24h; and the mildew resistance effect reaches 1 level.

[0073] Example 3

[0074] A multifunctional water-based paint that is stain-resistant, dirt-resistant, and acid-alkali-resistant is used for finishing the surface of wood floor paint, tile paint, or floor paint. The specific preparation method includes the following steps:

[0075] First, prepare a modified monomer. Hydrolyze 3 parts of 3-glycidyloxypropyltrimethoxysilane at pH 5.0 and 25°C for 2 hours to obtain a hydrolyzate; premix 1.5 parts of methacryloyloxyethyltrimethylammonium chloride with the hydrolyzate at 40°C for 1 hour to obtain a modified monomer. Preferably, this embodiment uses a higher content of modified monomer, which can significantly enhance the bonding strength between the coating and the substrate, and is particularly suitable for the treatment of smooth substrate surfaces.

[0076] Secondly, prepare a modified wear-resistant additive. The polyethylene wax is melted at 80°C, and hydrophobically modified silica with a particle size of 50 nm is added, with a mass ratio of 95:5. After high-speed shear dispersion for 30 minutes, the mixture is cooled and crushed to obtain 1 part of a nano-modified wear-resistant additive. In particular, the use of nano-silica with a larger particle size in this embodiment can form a microscopic rough structure on the coating surface, further improving the anti-fouling effect.

[0077] Then, the raw materials were weighed according to the following proportions: 80 parts of acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion (monomer mass ratio of 55:40:5, solid content 60%), 0.6 parts of polydimethylsiloxane defoamer, 0.8 parts of polyether modified polysiloxane leveling agent, 10 parts of film-forming aid mixed with ethylene glycol butyl ether and propylene glycol methyl ether (mass ratio of 1:1), 5 parts of polytetrafluoroethylene wax emulsion, 0.2 parts of mildew and fungicide mixed with isothiazolinone and hexamidine di(hydroxyethyl sulfonic acid) salt in a ratio of 1:1, 0.6 parts of polyoxyethylene-polyoxypropylene block copolymer (mass ratio of polyoxyethylene segment to polyoxypropylene segment of 35:65), 0.6 parts of povidone-iodine complex, and 60 parts of water.

[0078] Preferably, this embodiment adopts an emulsion system with a higher solid content, improves the hardness of the coating by increasing the proportion of methyl methacrylate, and adopts a mixed film-forming aid to balance the film-forming performance and the volatilization rate.

[0079] Next, the components were mixed in groups. The above components were divided into three groups: the first group was water, wetting agent and modified monomer; the second group was acrylic emulsion, polytetrafluoroethylene wax emulsion, modified wear-resistant additive and defoaming agent; the third group was povidone-iodine complex, mildew-proof fungicide and leveling agent. The three groups of mixtures were added to the reactor in sequence and stirred at 1100 rpm for 40 minutes.

[0080] Finally, a sand mill was used to grind the mixture at a rotation speed of 2200 rpm for 40 minutes, and the grinding fineness was controlled to be 20 μm, thereby obtaining the water-based coating.

[0081] Application method:

[0082] The water-based coating prepared above was mixed with a water-based epoxy resin curing agent in a weight ratio of 20:1, wherein the water-based epoxy resin curing agent was prepared by reacting a bisphenol A epoxy resin with a water-soluble amine in an equivalent ratio of 1:1.5, and polyoxyethylene alcohol ether with an HLB value of 14 was used as a non-ionic surfactant for emulsification to obtain a water-based epoxy resin curing agent with a solid content of 65%.

[0083] During construction, the surface of the substrate is polished, and the coating viscosity is adjusted to 300K.CUs and the pH value is adjusted to 10.0. Airless spraying is used for construction, and the coating thickness is controlled at 180-200μm. Curing is carried out for 24 hours at a temperature of 30℃ and a relative humidity of 70%.

[0084] Example 4

[0085] A multifunctional water-based paint that is stain-resistant, dirt-resistant, and acid-alkali-resistant is used for finishing the surface of wood floor paint, tile paint, or floor paint. The specific preparation method includes the following steps:

[0086] First, prepare the modified monomer. Hydrolyze 1.5 parts of 3-glycidyloxypropyltrimethoxysilane at pH 4.8 and 25°C for 2 hours to obtain a hydrolyzate; premix 0.8 parts of methacryloyloxyethyltrimethylammonium chloride with the hydrolyzate at 40°C for 1 hour to obtain a modified monomer. By precisely controlling the hydrolysis conditions, the moderate hydrolysis of the silane group is ensured to achieve the best interface bonding effect.

[0087] Secondly, prepare a modified wear-resistant additive. Polyethylene wax is melted at 80°C, and hydrophobically modified silica with a particle size of 30 nm is added, with a mass ratio of 95:5. After high-speed shear dispersion for 30 minutes, the mixture is cooled and crushed to obtain 0.5 parts of a nano-modified wear-resistant additive. In this embodiment, nano-silica with a medium particle size is selected, which can provide good wear resistance while maintaining good dispersibility.

[0088] Then, the raw materials were weighed according to the following proportions: 77 parts of acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion (monomer mass ratio of 58:37:5, solid content 55%), 0.4 parts of polydimethylsiloxane defoamer, 0.6 parts of polyether modified polysiloxane leveling agent, 8 parts of propylene glycol methyl ether film-forming aid, 4 parts of polytetrafluoroethylene wax emulsion, 0.15 parts of a 1:1 mixed mildew and fungicide of isothiazolinone and hexamidine di(hydroxyethyl sulfonic acid) salt, 0.5 parts of a polyoxyethylene-polyoxypropylene block copolymer (polyoxyethylene segment to polyoxypropylene segment mass ratio of 40:60) wetting agent, 0.5 parts of a povidone-iodine complex, and 65 parts of water.

[0089] In particular, this embodiment adopts a moderate monomer ratio and solid content to achieve an optimal balance of various properties.

[0090] Next, the components were mixed in groups. The above components were divided into three groups: the first group was water, wetting agent and modified monomer; the second group was acrylic emulsion, polytetrafluoroethylene wax emulsion, modified wear-resistant additive and defoamer; the third group was povidone-iodine complex, mildew-proof fungicide and leveling agent. The three groups of mixtures were added to the reactor in sequence and stirred at 1150 rpm for 40 minutes.

[0091] Finally, a sand mill was used to grind the mixture at a rotation speed of 2300 rpm for 35 min, and the grinding fineness was controlled to be 25 μm, thereby obtaining the water-based coating.

[0092] Application method:

[0093] The water-based coating prepared above was mixed with a water-based polyurethane curing agent in a weight ratio of 20:1, wherein the water-based polyurethane curing agent was prepared by reacting an isocyanate trimer with a polyether polyol in an equivalent ratio of 1:1, and was emulsified with a polyoxyethylene fatty alcohol ether with an HLB value of 13 as a nonionic surfactant to obtain a water-based polyurethane curing agent with a solid content of 60%.

[0094] During construction, after grinding the substrate surface, adjust the coating viscosity to 200K.CUs and the pH value to 9.5. Use a brush to apply the coating with a thickness of 150-180μm. Curing for 24 hours at a temperature of 27°C and a relative humidity of 65%.

[0095] Through the above four embodiments, the range of various process parameters is fully covered, fully demonstrating the feasibility and excellent performance of the present invention. The changes in raw material ratios and process parameters in different embodiments reflect the adaptability and stability of the present invention. Each embodiment is optimized for a specific application scenario to achieve a balance between different performance requirements.

[0096] Comparative Example 1

[0097] To verify the synergistic effect of the modified monomers, referring to the formula and process of Example 1, only 3-glycidyloxypropyltrimethoxysilane and methacryloyloxyethyltrimethylammonium chloride modified monomers were added separately, and the other components and preparation process remained unchanged.

[0098] Preferably, this comparative example is intended to illustrate the key role of the premixing treatment of the two modified monomers on the coating performance. The results show that when any component is used alone, the coating adhesion level is only 2-3, while in Example 1, it can reach level 0 after premixing modification. This is mainly due to the synergistic effect of the two monomers formed during the premixing process: the silane group provides an interface binding site, and the quaternary ammonium salt group enhances the coating adhesion through electrostatic action. The chemical synergy of the two is significantly better than the simple superposition effect when used alone.

[0099] Comparative Example 2

[0100] A control group was designed to use only polytetrafluoroethylene wax emulsion without adding nano-modified wear-resistant additives for the wear-resistant system of Example 2. In the specific preparation method, the preparation step of the wear-resistant additive was omitted, and other process parameters remained unchanged.

[0101] The test found that the Taber wear resistance of the comparative sample decreased significantly, with a mass loss of 120 mg, which is much lower than the performance level of Example 2. This fully proves the importance of nano-silicon dioxide modified wax wear-resistant additives in the system: through the reinforcing effect of nanoparticles and the lubricating effect of wax, a "hard-soft combination" synergistic protection mechanism is formed.

[0102] Comparative Example 3

[0103] To verify the advantages of the mildew-proof and sterilization system, the formula of Example 3 was used with reference to the formula of Example 3, but only the traditional isothiazolinone mildew-proof agent was used, and the povidone-iodine complex and hexamidine di(hydroxyethyl sulfonate) salt were removed. The preparation process was the same as that of Example 3.

[0104] The test results show that the control sample has obvious mold after 14 days of the mold test, and the mold resistance level is level 3, while Example 3 still maintains the level of level 1 after 30 days. This shows that the triple synergistic mold resistance system designed in the present invention has significant advantages: isothiazolinone provides rapid bactericidal effect, hexamidine salt ensures durability, and povidone-iodine fills the time window between the two through sustained release.

[0105] Comparative Example 4

[0106] A control experiment with different monomer ratios was designed for the emulsion system of Example 4. The mass ratio of acrylic acid, methyl methacrylate and acrylamide was adjusted to 50:45:5, and the other components and processes remained unchanged.

[0107] The test found that due to the high proportion of methyl methacrylate, the coating was too rigid and easily cracked in the impact test. This verifies the innovation of the present invention in the monomer ratio: by precisely controlling the ratio of the three monomers, the best balance between hardness and toughness is achieved.

[0108] Comparative Example 5

[0109] In order to investigate the effect of the selection of film-forming aids on the coating properties, the formulation of Example 1 was referred to, but ethylene glycol butyl ether was replaced with traditional triethylene glycol monobutyl ether, and the dosage remained unchanged.

[0110] The results show that the samples using the traditional film-forming aids have incomplete film formation at low temperatures (5°C), while the modified film-forming aid system used in the present invention can still maintain good film-forming performance even under low temperature conditions. This is mainly due to the film-forming aids selected in the present invention having more suitable volatilization rates and dissolution parameters.

[0111] Comparative Example 6

[0112] A one-step control experiment was designed for the dispersion method in the preparation process: all the components in Example 2 were directly mixed and stirred and dispersed under the same conditions.

[0113] The experimental results show that the sample prepared by the one-step method has stability problems and obvious stratification occurs after storage for 7 days. This verifies the necessity of the three-step dispersion process of the present invention: through a reasonable feeding sequence and step-by-step operation, mutual interference between functional components is effectively avoided, ensuring the long-term stability of the product.

[0114] The above comparative experiments fully demonstrate the innovations of the present invention in terms of formula composition, process design, etc., and there is an obvious synergistic effect between the functional components, and the overall performance is significantly better than the existing technology level. In particular, the improvement in key indicators such as wear resistance, mildew resistance and adhesion has important practical value.

[0115] The present invention relates to the performance testing and evaluation of a multifunctional anti-fouling, dirt-resistant and acid-alkali-resistant water-based coating, and mainly conducts a systematic evaluation on the physical and mechanical properties, chemical resistance and functional properties of the coating.

[0116] Test methods and standards:

[0117] Adhesion test:

[0118] According to GB / T9286-1998 standard, the test is carried out by cross-cutting method. A grid with a spacing of 1mm is drawn on the surface of the coating, and the shedding is observed after peeling with tape. The rating standard is 0-5, where 0 means no shedding and 5 means the shedding area exceeds 65%.

[0119] Wear resistance test:

[0120] According to GB / T4893.8-2013, the test was conducted using a Taber abrasion tester. A CS-17 grinding wheel was used, with a load of 1000g, and the mass loss after 1000 revolutions was tested. Preferably, this test can reflect the wear and dirt resistance of the coating, and can particularly reflect the enhancement effect of the nano-modified wear-resistant additive.

[0121] Chemical resistance test:

[0122] Refer to GB / T1733-1993 for acid and alkali resistance test. Use 10% sulfuric acid and 10% sodium hydroxide solution respectively, soak at 23±2℃ for 24h and observe the changes in coating appearance. Rating standard:

[0123] Excellent: No changes;

[0124] Good: slight discoloration but no blistering or shedding;

[0125] Acceptable: Slightly blistering but recoverable;

[0126] Unacceptable: obvious bubbling or peeling.

[0127] Anti-mildew performance test:

[0128] According to GB / T24346-2009, the Aspergillus niger was inoculated and cultured at 28±2℃ and relative humidity above 90% for 28 days, and the growth of mold was observed. The rating is 0-4, with 0 indicating no mold growth.

[0129] In particular, the present invention also designs the following innovative testing methods:

[0130] Interface bonding test:

[0131] The improved tensile peeling method is used to test the bonding strength between the coating and the substrate. A universal testing machine is used with a tensile speed of 50 mm / min to record the peeling force curve. This test can directly reflect the interface enhancement effect of the modified monomer.

[0132] Self-cleaning performance evaluation:

[0133] Drop the oily dye aqueous solution on the coating surface inclined at 45°, and observe the rolling angle and residual condition of the droplet. This method can evaluate the antifouling and self-cleaning performance of the coating.

[0134] According to the above test method, all embodiments and comparative examples were systematically tested, and the results were as follows:

[0135] Table 1 Test results of basic physical properties of coatings

[0136]

[0137] Table 2 Test results of coating chemical resistance

[0138]

[0139]

[0140] Table 3 Coating functional performance test results

[0141]

[0142] Based on the above test results analysis:

[0143] Example 3 exhibits the best comprehensive performance, especially in terms of key indicators such as wear resistance, mildew resistance and interface bonding strength, which all reach the best level. This is mainly due to the synergistic effects of the following aspects:

[0144] 1. Optimized ratio of modified monomers: A high content (3 parts) of 3-glycidyloxypropyltrimethoxysilane and an appropriate amount (1.5 parts) of methacryloyloxyethyltrimethylammonium chloride form an ideal interface modification structure, which significantly improves the interface bonding strength of the coating (3.8MPa). At the same time, the introduction of quaternary ammonium salt groups also provides additional antibacterial effects.

[0145] 2. Nanocomposite reinforcement mechanism: The hydrophobically modified silica with a particle size of 50 nm forms a special microstructure in the coating, which synergizes with the polytetrafluoroethylene wax emulsion to not only provide excellent wear resistance (mass loss is only 45 mg), but also achieves a high contact angle of 118°, giving the coating excellent self-cleaning properties.

[0146] 3. Multiple protection network structure: The high solid content (60%) ternary copolymer emulsion forms a dense cross-linked network during the film-forming process by optimizing the monomer ratio (55:40:5). This network structure forms a multi-level synergistic protection system with modified monomers and nanoparticles, significantly improving the comprehensive protection performance of the coating.

[0147] In addition, the present invention also has the following unexpected technical effects:

[0148] 1. Ultra-long-lasting mildew-proof performance: It was originally expected that the mildew-proof effect could last for 14 days, but the test found that Example 3 still maintained the level of 0 after 28 days. In-depth research found that this was because the quaternary ammonium salt group and povidone-iodine formed a unique synergistic release mechanism, achieving a sustained and stable mildew-proof effect.

[0149] 2. Self-repairing performance: It was unexpectedly found during the wear test that the sample of Example 3 can recover by itself at room temperature after being slightly scratched. This self-repairing effect is attributed to the dynamic reversible bonds formed by the modified monomer in the network structure, which provides additional durability for the coating.

[0150] 3. Synergistic enhancement effect: The combination of nanoparticles and wax emulsion not only provides the expected wear resistance, but also significantly improves the chemical resistance of the coating through interfacial interaction, especially in terms of acid and alkali resistance, which exceeds the effect of the addition of a single component.

[0151] By comparing the test results, it can be seen that the present invention achieves a comprehensive improvement in coating performance through multiple synergistic mechanisms, especially in key indicators such as chemical resistance, mildew resistance and self-cleaning, which is far superior to the existing technology level and has important practical value and innovative significance.

[0152] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A multifunctional anti-fouling, dirt-resistant, acid-base resistant water-based paint for finishing the surface of wood floor paint, tile paint or floor paint, characterized in that: The parts by weight include: 70-80 parts of acrylic emulsion, 0.5-1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride, 1-3 parts of 3-glycidyloxypropyl trimethoxy silane, 0.2-0.6 parts of povidone-iodine complex, 0.2-0.6 parts of polydimethylsiloxane defoamer, 0.3-0.8 parts of polyether modified polysiloxane leveling agent, 4-10 parts of film-forming aid, 0.2-1 parts of nano-silicon dioxide modified wax wear-resistant additive, 3-5 parts of polytetrafluoroethylene wax emulsion, 0.1-0.2 parts of mildew and fungicide, 0.2-0.6 parts of non-ionic polyether wetting agent, 60-70 parts of water; Wherein, the acrylic emulsion is an acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion with a solid content of 50%-60%.

2. The water-based paint according to claim 1, characterized in that: The film-forming aid is selected from ethylene glycol butyl ether, propylene glycol methyl ether and a mixture thereof; The mildew-proofing and fungicide is a mixture of isothiazolinone and hexamidine di(hydroxyethylsulfonic acid) salt in a weight ratio of 1:1; The nano-silicon dioxide modified wax wear-resistant additive is prepared by mixing polyethylene wax and hydrophobic modified silicon dioxide with a particle size of 20-50 nm in a weight ratio of 95:

5.

3. The water-based paint according to claim 1, characterized in that: In the acrylic acid-methyl methacrylate-acrylamide ternary copolymer emulsion, the mass ratio of acrylic acid, methyl methacrylate and acrylamide is 60:35:5, and the solid content is 55%.

4. The water-based paint according to claim 1, characterized in that: The added amount of the methacryloyloxyethyltrimethylammonium chloride is 1 part, The amount of 3-glycidyloxypropyltrimethoxysilane added is 2 parts, The added amount of the povidone-iodine complex is 0.4 parts.

5. The method for preparing a water-based coating according to claim 1, characterized in that: The following steps are involved: (1) Preparation of modified monomers: 3-Glycidyloxypropyltrimethoxysilane was hydrolyzed at pH 4-5 and 25°C for 2 h; Methacryloxyethyltrimethylammonium chloride and hydrolyzed 3-glycidyloxypropyltrimethoxysilane were premixed at 40 °C for 1 h; (2) Preparation of modified wear-resistant additives: The polyethylene wax was melted at 80°C, hydrophobically modified silica was added, dispersed at high speed for 30 minutes, and then cooled and crushed; (3) Grouping and mixing: The first group: water, a nonionic polyether wetting agent and the modified monomer obtained in step (1); The second group: acrylic emulsion, polytetrafluoroethylene wax emulsion, the modified wear-resistant additive obtained in step (2) and polydimethylsiloxane defoaming agent; The third group: povidone-iodine complex, mildew-proof fungicide and polyether-modified polysiloxane leveling agent; (4) Add the three mixtures into the reactor in sequence and stir at 1000-1200 rpm for 40 min; (5) Grinding with a sand mill at a rotation speed of 2000-2500 rpm for 30-40 min, controlling the grinding fineness to be ≤30 μm, to obtain the water-based coating.

6. The preparation method according to claim 5, characterized in that: The preparation method of the hydrophobically modified silica is: The fumed silica was vacuum dried at 110-130°C for 2 h, dimethyldichlorosilane was added, refluxed under nitrogen protection for 4 h, filtered, washed with toluene 3 times, and dried at 80°C for 12 h.

7. The preparation method according to claim 5, characterized in that: The nonionic polyether wetting agent is a polyoxyethylene-polyoxypropylene block copolymer, wherein the mass ratio of the polyoxyethylene segment to the polyoxypropylene segment is 40:

60.

8. The method for applying a water-based paint according to claim 1, characterized in that: The water-based paint and curing agent are mixed in a weight ratio of 20:1 and then applied. Wherein, the curing agent is selected from at least one of a water-based epoxy resin curing agent and a water-based polyurethane curing agent.

9. The application method according to claim 8, characterized in that: The viscosity of the water-based paint during brushing is 150-300K.CUs, and the pH value is 9-10. The coating curing temperature is 25-30°C, the relative humidity is 50-70%, and the curing time is 24h.

10. The application method according to claim 8, characterized in that: The curing agent is a modified waterborne epoxy resin curing agent, which is prepared by reacting epoxy resin and water-soluble amine at an equivalent ratio of 1:1.2 and emulsifying with a non-ionic surfactant.

Citation Information

Patent Citations

  • Nano-silicon dioxide loaded wax water-based dispersion, and preparation method and use thereof

    CN103467829A

  • Waterborne woodware matte white finish with high scratch resistance and high performance

    CN105440835A

  • Highly weather-resistant waterborne mildewproof varnish for wooden ware

    CN107858055A

  • Special aqueous full-matte finishing varnish for faux limestone and preparation method for special aqueous full-matte finishing varnish

    CN110527363A

  • Water-based anti-skid overlay for ceramic tile and preparation method and application thereof

    CN110724421A

Cited By

  • Anti-condensation corrosion-resistant super-hydrophobic coating material based on micro-nano composite structure and preparation method of anti-condensation corrosion-resistant super-hydrophobic coating material

    CN122146151A

  • A micro-nano composite structure-based anti-condensation corrosion-resistant super-hydrophobic coating material and a preparation method thereof

    CN122146151B